1981
DOI: 10.1084/jem.154.1.138
|View full text |Cite
|
Sign up to set email alerts
|

J chain biosynthesis in pre-B cells and other possible precursor B cells.

Abstract: Human cell lines that resemble precursors in the B cell lineage have been found to synthesize J chain. In vivo pulse labeling, together with in vitro translation of total cellular RNA in a wheat germ cell-free system, detected the synthesis of J chain in immunoglobulin-secreting cell lines, in a cell line with only surface IgM, as well as in the pre-B-like cell line Josh 4 and the round cell lines Josh 7 and KLM 2. The primary translation products of J chain from all of these cell lines were found to be indist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0
1

Year Published

1986
1986
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(21 citation statements)
references
References 21 publications
2
18
0
1
Order By: Relevance
“…The expression of J chain in cells that are not engaged in the synthesis of polymers has been interpreted as a sign of clonal immaturity (Brandtzaeg, 1985). Extensive studies of human cells from leukemia patients, established lymphoid cell lines, and Epstein-Barr virus (EBV)-transformed fetal bone marrow cells (depleted of surface Ig-positive cells) revealed that J chain may be expressed in the cytoplasm of human lymphocytes from the earliest stages of their differentiation along the B cell axis (McCune et al, 1981;Kutteh et al, 1983;Hajdu et al, 1983;Max and Korsmeyer, 1985;Kubagawa et al, 1988;Mestecky et al, 1977Mestecky et al, , 1997. Thus, cells phenotypically characterized as null, pro-, or pre-B cells contain J chain, frequently in the absence of μ chain.…”
Section: Figurementioning
confidence: 98%
“…The expression of J chain in cells that are not engaged in the synthesis of polymers has been interpreted as a sign of clonal immaturity (Brandtzaeg, 1985). Extensive studies of human cells from leukemia patients, established lymphoid cell lines, and Epstein-Barr virus (EBV)-transformed fetal bone marrow cells (depleted of surface Ig-positive cells) revealed that J chain may be expressed in the cytoplasm of human lymphocytes from the earliest stages of their differentiation along the B cell axis (McCune et al, 1981;Kutteh et al, 1983;Hajdu et al, 1983;Max and Korsmeyer, 1985;Kubagawa et al, 1988;Mestecky et al, 1977Mestecky et al, , 1997. Thus, cells phenotypically characterized as null, pro-, or pre-B cells contain J chain, frequently in the absence of μ chain.…”
Section: Figurementioning
confidence: 98%
“…In contrast, Erlandsson, et al, using diphtheria toxin A (DTA) targeting to the J-chain locus, found that cells are clonally marked from an early stage of development to be either J-chain-positive or -negative, long before they become Ig-secreting cells (20) (Figure 2D). In humans, J-chain expression has also been described in early B cell development, prior to antigen receptor expression (2, 69, 77, 78), but how this early J-chain expression fits in with “clonally marked” J-chain-positive or -negative cells is unclear.…”
Section: Populations Of J-chain Expressing and Non-expressing Plasma mentioning
confidence: 99%
“…Consequently, this peptide is found in all polymeric forms of IgA [96,99]. Polymerisation of two or more IgA molecules with the J chain occurs late in the secretory pathway, just before release from plasma cells [61].…”
Section: Structure Of Igamentioning
confidence: 99%